Gender Norms and Economic Empowerment Intervention to Reduce Intimate Partner Violence Against Women in Rural Côte D'ivoire : A Randomized Controlled Pilot Study - Gupta, Jhumka (World Bank, Washington, DC, 2014)
Gender-based violence against women, including intimate partner violence (IPV), is a pervasive health and human rights concern. However, relatively little intervention research has been conducted on how to reduce IPV in settings impacted by conflict. The current study reports on the evaluation of the incremental impact of adding gender dialogue groups to an economic empowerment group savings program on levels of IPV. This study took place in north and northwestern rural Côte d Ivoire.